Relationship of Bananas (Musa spp.) Based on Morphological Characteristics in Sungai Pinyuh District, Mempawah Regency - Rochmah, Febri Aini; Ifadatin, Siti; Linda, Riza (Jurnal Biologi Tropis, 2024)
Bananas (Musa spp.) are herbaceous plant members of the Musaceae family, which has different morphological characters. This study aims to identify the relationship between banana cultivars based on morphological characteristics. The research was done from August to November 2022 in Sungai Pinyuh District, Mempawah Regency. This research used the exploratory method with the purposive sampling technique and was then analyzed using the UPGMA method through the Numeric Taxonomy and Multivariate System (NTSYS version 2.0) program. The bananas from Sungai Pinyuh regency consist of kepok banana, ambon banana, forty-day banana, barangan banana, awak banana, and kak mirah banana. The results of the banana relatedness analysis show a similarity level of 0.44, which is divided into two groups, A and B. Group A consists of 3 cultivars, namely banana kepok, banana awak, and banana kak mirah; group B consists of 3 cultivars, namely banana ambon, banana barangan, and banana forty days.